Unconventional intronic splice site mutation in SCN5A associates with cardiac sodium channelopathy. Issue 5 (29th April 2005) - Rossenbacker, T; Schollen, E; Kuipéri, C; de Ravel, T J L; Devriendt, K; Matthijs, G; Collen, D; Heidbüchel, H; Carmeliet, P
Abstract : Background: Mutations in the cardiac sodium channel, SCN5A, have been associated with one type of long-QT syndrome, with isolated cardiac conduction defects and Brugada syndrome. The sodium channelopathies exhibit marked variation in clinical phenotypes. The mechanisms underlying the phenotypical diversity, however, remain unknown. Exonic SCN5A mutations can be detected in 20% of Brugada syndrome patients. Results: An intronic mutation (c.4810+3_4810+6dupGGGT) in the SCN5A gene, located outside the consensus splice site, was detected in this study in a family with a highly variable clinical phenotype of Brugada syndrome and/or conduction disease and in a patient with Brugada syndrome. The mutation was not found in a control panel of 100 (200 alleles) ethnically matched normal control subjects. We provide in vivo and in vitro evidence that the mutation can disrupt the splice donor site, activate a cryptic splice site, and create a novel splice site. Notably, our data show that normal transcripts can be also derived from the mutant allele. Conclusions: This is the first report of an unconventional intronic splice site mutation in the SCN5A gene leading to cardiac sodium channelopathy. We speculate that its phenotypical diversity might be determined by the ratio of normal/abnormal transcripts derived from the mutant allele.